Telemedicine as a health care strategy for persons deprived of liberty: an experience report - Costa, Marta Cossetin; Arze, Wilma Nancy Campos; Campos, Adriel Chihyun Chung (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Telemedicine is a tool for overcoming geographical and physical barriers in the process of guaranteeing health care. Objective: To report the experience of medical care mediated by information and communication technologies to persons deprived of liberty at two penal units in the west side of Paraná, Brazil. Methods: This is a quantitative, qualitative, descriptive experience report. Results: Medical care mediated by information and communication technologies is an additional tool, based on multidisciplinary care practices, in the search for the right to health care to persons deprived of liberty. Conclusion: This experience allowed a reflection on the health and health care of the prisons’ population, with information and communication technologies placed as a tool to bring the academic environment and the penal unit together in the search for comprehensive health care.